Thermocatalytic Decomposition of Methane and Methane/Methanol Mixture Over Ni-based Catalysts - AWAD, ALI (2018)
Thermocatalytic decomposition (TCD) over Ni-based catalysts has gained sufficient interest in producing H2 and elemental carbon by non-oxidative decomposition of hydrocarbons.